The Efficacy of Short Pre-sessional Courses on Learner Writing - Bridle, Marcus Adrian (Journal of Academic Writing, 2021)
This study examines the development of learner written accuracy over the course of a short, university pre-sessional course. One of the issues practitioners and learners are faced with on short courses is the time limitation, which can result in an emphasis on the macros-linguistic, organisational features of academic writing at the expense of a focus on written accuracy. The research charted the effects of an error feedback and revision cycle on student writing. The key observations were that the majority of revisions were made successfully and that this may have contributed towards the subsequent written accuracy of drafts. These findings suggest that, contrary to some perceptions, short pre-sessional courses can have a positive effect on the linguistic accuracy of learner writing.